2021
DOI: 10.1038/s41598-021-91149-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid manufacturing of micro-drilling devices using FFF-type 3D printing technology

Abstract: Micro-drilling devices with different blade shapes were fabricated with a rapid and facile manufacturing process using three-dimensional (3D) printing technology. The 3D-printed casting mold was utilized to customize the continuous shape of the blades without the need for expensive manufacturing tools. A computational fluid dynamics simulation was performed to estimate the pressure differences (fluidic resistance) around each rotating device in a flowing stream. Three types of blades (i.e., 45°, 0°, and helica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Te commercially available tungsten carbide drill bit of diameter 0.5, 0.7, and 0.9 mm, with the angle of the 45 °fute is used in the present study. Among the considered blades (45 °, 0 °, and helical type), 45 °blades exhibited the best drilling performance [28]. Te dimensions of the printed sample are convenient to adapt to the working table of the CNC machine.…”
Section: Methodsmentioning
confidence: 99%
“…Te commercially available tungsten carbide drill bit of diameter 0.5, 0.7, and 0.9 mm, with the angle of the 45 °fute is used in the present study. Among the considered blades (45 °, 0 °, and helical type), 45 °blades exhibited the best drilling performance [28]. Te dimensions of the printed sample are convenient to adapt to the working table of the CNC machine.…”
Section: Methodsmentioning
confidence: 99%
“…Originally used for rapid prototyping, 3D printing techniques have increasingly entered into the application areas of rapid manufacturing and rapid tooling [1][2][3]. Many typical 3D printing polymers, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The FDM method deposits a filament (e.g., polylactic acid or acrylonitrile butadiene styrene) layer-by-layer; however, the resulting product has a poor surface roughness[ 38 , 39 ]. Recent studies have revealed that this drawback (i.e., rough surface) can be intentionally utilized for various applications such as (super) hydrophobic surfaces[ 40 ], micro-drilling devices[ 41 ], microchannels[ 42 ], and non-sticky surfaces[ 43 ].…”
Section: Introductionmentioning
confidence: 99%